2008
DOI: 10.1158/1535-7163.mct-08-0617
|View full text |Cite
|
Sign up to set email alerts
|

Genistein down-regulates androgen receptor by modulating HDAC6-Hsp90 chaperone function

Abstract: Androgen receptor (AR) is a ligand-activated transcription factor belonging to the steroid hormone receptor family and is very important for the development and progression of prostate cancer. The soy isoflavone genistein has been shown previously to down-regulate AR in androgendependent prostate cancer cell lines such as LNCaP. However, the mechanism(s) by which AR is downregulated by genistein is still not known fully. We show a new mechanism by which genistein inhibits AR protein levels. We show that genist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 43 publications
(50 reference statements)
8
63
0
Order By: Relevance
“…The heat shock activator gedunin had a similar effect on ubiquitination in the cell, emphasizing the close connection between the heat shock and the ubiquitin-proteasome pathways. These data also corroborate previous studies that have found Hsp90 inhibition increases ubiquitination (42). The heat shock system was confirmed to be up-regulated upon treatment with each of the small-molecule compounds (Fig.…”
Section: L54r and L172h Mutant Dystrophins Are Degraded By The Proteasupporting
confidence: 91%
“…The heat shock activator gedunin had a similar effect on ubiquitination in the cell, emphasizing the close connection between the heat shock and the ubiquitin-proteasome pathways. These data also corroborate previous studies that have found Hsp90 inhibition increases ubiquitination (42). The heat shock system was confirmed to be up-regulated upon treatment with each of the small-molecule compounds (Fig.…”
Section: L54r and L172h Mutant Dystrophins Are Degraded By The Proteasupporting
confidence: 91%
“…Besides known natural and synthetic agents, a number of different bioactive food components, such as quercitin (Aalinkeel et al 2008), genistein (Basak et al 2008), and epigallocatechin-3-gallate (Tran et al 2010), were also identified as potent HSP90 inhibitors. Modulation of post-translational mechanisms is an important approach to interfere with the regulation of HSP90.…”
Section: Influence Of Butyrate On Expression Levelsmentioning
confidence: 99%
“…Classical inhibitors like geldanamycin and its derivates as well as synthetic molecules block the ATPase-coupled chaperone cycle and consign bound client proteins for ubiquitination and proteosomal degradation (Pearl et al 2008). Targeting molecules that are involved in the regulation of HSP90, as for example histone deacetylase (HDAC) 6, is an alternative approach to inhibit chaperone activity (Pearl et al 2008) and was, inter alia, demonstrated for genistein (Basak et al 2008). Quercitin (Aalinkeel et al 2008) and epigallocatechin-3-gallate (Yin et al 2009) are further nutrition-related compounds with HSP90-inhibiting potential.…”
Section: Introductionmentioning
confidence: 99%
“…50 Genistein, an isoflavone, inhibits EGFR tyrosine kinase, 51 and also inhibits the Hsp90 deacetylase (HDAC6)-Hsp90 co-chaperone function, which downregulates the expression of androgen receptor in androgen-dependent prostate cancer cell lines. 52 Quercetin, a flavonoid, inhibits cancer cells that over-express ErbB2 (Her-2/neu) trans-membrane tyrosine kinase and downregulates the downstream PI3K-Akt signaling pathway. 53 Novobiocin binds to the C-terminal domain of Hsp90 and disrupts the Bcr-Abl/Hsp90 complex.…”
Section: Actions Ofmentioning
confidence: 99%